Relay Kontrol Menggunakan Google Firebase dan Node MCU pada Sistem Smart Home - Basri, Basri; Akhmad Qashlim; Suryadi (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2021)
The proper use of energy in the household has many benefits, not only for homeowners but saving energy can benefit human life. The problems that occur, sometimes people forget to turn off their electronic devices before leaving for work such as irons, air conditioners, TVs, fans, rice cookers, dispensers, and others. So that the consequence is that in addition to security issues, it can also lead to a waste of energy on the number of electricity bills. In this research, Smart Home Tools and Systems were designed to be able to control the lights and other electronic equipment using NodeMCU which has been integrated with a Wi-Fi chip so that it can be controlled by a Smartphone anywhere as long as there is internet access. The results obtained from this test were full control over the shutdown or turning on of several electronic devices using an android device connected to the internet so that homeowners don't have to bother returning home to turn off their electronic equipment.